Effect of a Patient Blood Management Program on the Appropriateness of Red Blood Cell Transfusion and Clinical Outcomes in Elderly Patients Undergoing Hip Fracture Surgery - Kim, Jong Hun; Shin, Hyeon Ju; You, Hae Sun; Park, Yoonsun; Ahn, Ki Hoon; Jung, Jae Seung; Han, Seung-Beom; Park, Jong Hoon (Journal of Korean medical science, 2023)
Elderly patients with hip fractures frequently receive perioperative transfusions, which are associated with increased morbidity and mortality. This study aimed to evaluate the impact of a patient blood management (PBM) program on the appropriateness of red blood cell (RBC) transfusion and clinical outcomes in geriatric patients undergoing hip fracture surgery. In 2018, the revised PBM program was implemented at the Korea University Anam Hospital, Seoul, Republic of Korea. Elderly patients aged ≥ 65 years who underwent hip fracture surgery from 2017 to 2020 were evaluated. Clinical characteristics and outcomes were analyzed according to the timing of PBM implementation (pre-PBM, early-PBM, and late-PBM). Multiveriate regression analysis was used to evaluate the risk factors of the adverse outcomes, such as in-hospital mortality or 30-day readmission. A total of 884 elderly patients were included in this study. The proportion of patients who received perioperative RBC transfusions decreased significantly (43.5%, 40.1%, and 33.2% for pre-PBM, early-PBM, and late-PBM, respectively; = 0.013). However, the appropriateness of RBC transfusion significantly increased (54.0%, 60.1%, and 94.7%, respectively; < 0.001). The duration of in-hospital stay and 30-day readmission rates significantly decreased. Multivariable regression analysis revealed that RBC transfusion (odds ratio, 1.815; 95% confidence interval, 1.137-2.899; = 0.013) was significantly associated with adverse outcomes. Implementing the PBM program increased the appropriateness of RBC transfusion without compromising transfusion quality and clinical outcomes. Therefore, adopting the PBM program may improve the clinical management of elderly patients following hip fracture surgery.